2005
DOI: 10.1291/hypres.28.727
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Reference Values for Both Total Soluble Fms-Like Tyrosine Kinase 1 and Free Placental Growth Factor in Pregnant Women

Abstract: It has been reported that the concentration of free placental growth factor (PIGF) is decreased and that of soluble fms-like tyrosine kinase 1 (sFlt-1) is increased before the onset of preeclampsia. However, no study has determined the reference values for sFlt-1 and free PIGF during pregnancy using a commercially available enzyme-linked immunosorbent assay (ELISA) kit. This longitudinal cohort study was undertaken to address this issue. Serum samples were collected from 148 women at 10, 18, 28, and 37 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 19 publications
11
47
1
Order By: Relevance
“…In normal pregnancy, the serum concentration of sFlt-1 decreases from 8-12 weeks to 16-20 weeks, gradually increases at 26-30 weeks, rapidly elevates at 35-39 weeks of gestation, and it is back to normal level after delivery [30,31]. However, sFlt-1 level in preeclamptic pregnancy is significantly higher than that of normal pregnancy.…”
Section: Sflt-1mentioning
confidence: 93%
See 1 more Smart Citation
“…In normal pregnancy, the serum concentration of sFlt-1 decreases from 8-12 weeks to 16-20 weeks, gradually increases at 26-30 weeks, rapidly elevates at 35-39 weeks of gestation, and it is back to normal level after delivery [30,31]. However, sFlt-1 level in preeclamptic pregnancy is significantly higher than that of normal pregnancy.…”
Section: Sflt-1mentioning
confidence: 93%
“…In addition, PlGF may be expressed in endothelial cells, natural killer cells, bone marrow cells, and keratinocytes [42]. In normal pregnancy, the serum concentration of PlGF increases from 8-12 weeks, reaches to peak at 29-32 weeks, and then decreases at 33-40 weeks of gestation [30,31]. PlGF levels in women who later had preeclampsia were significant lower than the controls from 13-16 weeks of gestation till delivery and the PlGF was lowest in women with clinical preeclampsia at similar gestational age [31].…”
Section: Plgfmentioning
confidence: 99%
“…7 Recently, it has been shown that two antiangiogenic peptides produced by the placenta, soluble fms-like tyrosine kinase 1 (sFlt-1) and soluble endoglin (sEng), contribute to the pathogenesis of PE. [8][9][10][11][12] Although the mechanisms of sEng through which hypertension and proteinuria occur have not been clearly clarified, 13 it is speculated that the increase of sFlt-1 weakens an action of placental growth factor (PlGF) or vascular endothelial growth factor-A, resulting in hypertension and proteinuria via endothelial injury. 14,15 In comparative studies of serum levels of sFlt-1, sFlt-1/PlGF ratio, sEng in women with GH and PE, the mean serum levels of sFlt-1, sFlt-1/PlGF ratio and sEng in women with PE were significantly higher than in women with GH; those in women with GH were higher than in control women.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,9,[15][16][17][18][19][20][21][22][23][24][25] In this study, we also revealed that a new and automated electrochemiluminescence immunoassay for plasma sFlt-1 and PlGF levels at 19-25 weeks of gestation had potential predictive power for predicting all PE. In our current study, the LR þ of the plasma level of the sFlt-1/PlGF ratio at 19-25 weeks for predicting all PE was 4.2, whereas in the previous study using an ELISA kit (R&D Systems, Minneapolis, MN, USA), the LR þ of the serum level of the sFlt-1/PlGF ratio at 19-25 weeks for predicting all PE was 4.7 (Ohkuchi et al 3 ).…”
Section: Discussionmentioning
confidence: 69%